FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR - Nadya Stevie Khanaya Siahaan (Bina Ekonomi, 2020)
Disclosure of CSR in a company is an important thing for companies to do. The government itself has also made regulations that require companies to disclose CSR. But in reality, there are still many companies that have not made CSR disclosures by not making a Sustainability Report. There are many factors that can affect CSR disclosure in a company. This study aims to determine whether these factors really affect CSR disclosure. The factors studied were company size, financial performance, and environmental performance. Company size is measured by the natural logarithm of the company's total assets, financial performance is measured by the Return on Assets ratio, environmental performance is measured by the PROPER rating, and CSR disclosure is measured by the number of components disclosed based on GRI standards. This research is a quantitative research with a causal form. This research was conducted on manufacturing companies in Indonesia that have published financial reports and sustainability reports from 2017 to 2019, namely 10 companies. The data that has been collected in this study was then tested using IBM SPSS Statistics 26 software with several forms of testing, namely descriptive statistical tests, classical assumption tests consisting of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, t statistic test, and test. F statistics. The results of this study are company size does not partially affect CSR disclosure, financial performance does not partially affect CSR disclosure, environmental performance does not partially affect CSR disclosure, and company size, financial performance, and environmental performance do not simultaneously affect CSR disclosure.